Small RNA Sequencing Revealed that miR4415, a Legume-Specific miRNA, was Involved in the Cold Acclimation of Ammopiptanthus nanus by Targeting an L-Ascorbate Oxidase Gene and Regulating the Redox State of Apoplast - Zhu, Ming; Wang, Xue; Zhou, Yanqiu; Tan, Jinhua; Zhou, Yijun; Gao, Fei (Frontiers in Genetics, 2022)
MicroRNAs (miRNAs) are small endogenous single-stranded RNAs that regulate plant growth, development, and environmental stress response post-transcriptionally. Ammopiptanthus nanus, a rare evergreen broad-leaved shrub in the temperate area of Central Asia, can tolerate the freezing stress as low as –30 degrees centigrade in winter, and miRNA might be involved in the cold acclimation which enables A. nanus to obtain the tolerance to freezing stress. Systematic identification and functional analysis of the miRNAs involved in the cold acclimation in A. nanus may promote understanding of the miRNA mediated gene regulation network underlying cold acclimation. Here, based on small RNA and degradome sequencing, 256 miRNAs and 1,808 miRNA-target pairs were identified in A. nanus. A total of 39 cold-responsive miRNAs were identified, of which 29 were upregulated and 10 were downregulated. These cold responsive miRNAs may participate in the cold acclimation by regulating redox homeostasis (miR398, miR4415, and miR408), calcium signaling (miR5225 and miR5211), growth and development (miR159 and miR390), and small RNA mediated gene silencing (miR168 and miR1515). We found that miR4415, a legume-specific miRNA, is involved in the cold acclimation of A. nanus by targeting a L-ascorbate oxidase gene and then regulating the redox state of apoplast. Our study provides important data for understanding the regulatory role of miRNA in cold acclimation of A. nanus.